Financial Market Capitalism and Labour in Germany. Merits and Limits of a Sociological Concept. Issue 3 (2nd July 2020) - Haipeter, Thomas
Abstract : Since the financial crisis at the end of the last decade, Germany is regarded again as a successful coordinated market economy. However, a closer look at labour and working conditions reveals disturbing phenomena like an increase of psychical stress, growing shares of low wage employment or the erosion of collective bargaining or works councils' coverage. Finance capitalism has become the most popular concept among German sociologists to explain why and how industrial relations and working conditions have been put under pressure in the last one or two decades. But how coherent is the finance capitalism story? This question is tackled in the paper, based on literature review and empirical findings. The paper argues that the concept is overexpanded and that, first, financial market capitalism is refractured by agency and actors on different instituitonal levels and that, second, there are other and independent developments influencing industrial relations like globalisation or the deregulation of labour markets that have to be taken into account.